Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

Ecological risks and recent inputs of banned and current-use pesticides in surface water and sediment from Malawi's tobacco-growing region - Emmanuel Cishibanji; Rodgers Makwinja; Elias Chirwa; Benjamin N. Kondowe; John Kamanula; Christopher J. Curtis; Fabrice Muvundja; Bossissi Nkuba (Environmental Pollution, 2026)

Evaluating the evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards - Jason J. Kolbe; Jacob D. Ward; C. Mike Norris; John Rodgers; Sydney Wayne; Daniel A. Warner (Evolutionary Ecology, 2026)
Whether phenotypic plasticity facilitates adaptive evolution is a key question in evolutionary ecology. The discovery of limb-length plasticity in two Anolis lizard species led to hypotheses about its role in the Anolis radiation. Yet, whether limb plasticity is realized in nature and has adaptive significance is poorly understood. In this study, we combined a limb-length plasticity experiment, lab-based assays of hatchling behavior, and field-based measures of individual perch-diameter use of hatchling A. sagrei . We compared our findings to previous lab experiments and field studies to better understand the ecological conditions that might elicit limb plasticity and influence the adaptive potential of limb-length in Anolis lizards. Results from our lab experiment did not support limb-length plasticity. Significant limb-length differences due to plasticity were found in some previous experiments but not others. Intriguingly, repeated observations of individual hatchlings at night revealed consistent use of narrow-diameter perches for an island population. In contrast, individual diurnal perch-diameter use in adult A. sagrei was much less uniform. Little evidence exists for adaptive behavior or performance in hatchlings related to limb length and perch diameters. Several aspects of anole behavior and ecology, such as perch preferences and sleep-site use, influence perch-diameter use. Differences among populations in hindlimb length for Bahamian islands often exceed the average plastic response found in lab experiments. Evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards is currently mixed. A better understanding of how perch-diameter use results in biomechanical and developmental cues that influence limb growth is needed. The lack of clear support from lab and field studies urges caution when hypothesizing about the role of limb-length plasticity in the Anolis radiation.

Application of Gon's algorithm to monitor productivity using Sentinel-2 Multi-spectral Instrument in Lake Kyoga, Uganda - John Peter Obubu; Yoshihiko Inagaki; Rodgers Makwinja; Tatsuyuki Sagawa; Rebecca Walugembe Nambi (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

The Microbial Trojan Horse and Antimicrobial Resistance: Acanthamoeba as an Environmental Reservoir for Multidrug Resistant Bacteria - Ronnie Mooney; Erin Corbett; Elisa Giammarini; Kiri Rodgers; Carla Donet; Ernest Mui; Arhama T. A. Ansari; Ayush Ransingh; Pradnya S. Vernekar; Harleen K. Walia; Jyoti Sharma; John Connolly; et al. (Environmental Microbiology, 2025)
Antimicrobial resistance (AMR) is shaped by environmental pressures, yet the role of microbial predators such as Acanthamoeba in resistance dynamics remains poorly characterized. In this study, Acanthamoeba ‐associated bacterial communities (AAB) exhibited significantly higher multidrug resistance than sediment‐associated bacterial communities (SAB) in a polluted estuarine system. All isolated amoebae belonged to the T4 genotype, suggesting selection for resilient host organisms. AAB displayed elevated multiple antibiotic resistance (MAR) indices and increased resistance to multiple antibiotic classes, particularly aminoglycosides, macrolides, fluoroquinolones and β‐lactams. Correlation analysis revealed that resistance in AAB, but not SAB, was associated with potentially toxic elements (PTEs) known to influence phagocyte survival, including arsenic, vanadium, and calcium. These elements may select for traits that confer metal and antibiotic resistance. The findings support a model where protists act as selective environments for AMR, favoring bacteria that possess enhanced tolerance mechanisms. This work provides the first direct evidence linking PTE exposure to the intracellular resistome of Acanthamoeba ‐associated bacteria. It underscores the need for AMR monitoring frameworks that include protist‐bacteria interactions, with implications for One Health and environmental risk assessment strategies. Moreover, this approach is scalable for application in low/middle‐income countries, where AMR burden is greatest and surveillance capacity remains limited.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Extended one-generation reproductive toxicity study of food-grade titanium dioxide E171 with emphasis on reproductive and endocrine endpoints - Rodger V. Battersby; Janine Adam; Amy L. Williams; John M. DeSesso (Reproductive Toxicology, 2024)

Stable hydrogen isotope evidence of late-Holocene precipitation variability on the Caribbean slope of the Cordillera Central, Costa Rica - Phyllis Y.Y. Kho; Chad S. Lane; Sally P. Horn; John C. Rodgers; Douglas W. Gamble (Quaternary International, 2024)

Beat-to-beat blood pressure variability, hippocampal atrophy, and memory impairment in older adults - Trevor Lohman; Isabel Sible; Allison C. Engstrom; Arunima Kapoor; Fatemah Shenasa; Elizabeth Head; Lorena Sordo; John Paul M. Alitin; Aimee Gaubert; Amy Nguyen; Kathleen E. Rodgers; David Bradford; et al. (GeroScience, 2024)
Visit-to-visit blood pressure variability (BPV) predicts age-related hippocampal atrophy, neurodegeneration, and memory decline in older adults. Beat-to-beat BPV may represent a more reliable and efficient tool for prospective risk assessment, but it is unknown whether beat-to-beat BPV is similarly associated with hippocampal neurodegeneration, or with plasma markers of neuroaxonal/neuroglial injury. Independently living older adults without a history of dementia, stroke, or other major neurological disorders were recruited from the community ( N = 104; age = 69.5 ± 6.7 (range 55–89); 63% female). Participants underwent continuous blood pressure monitoring, brain MRI, venipuncture, and cognitive testing over two visits. Hippocampal volumes, plasma neurofilament light, and glial fibrillary acidic protein levels were assessed. Beat-to-beat BPV was quantified as systolic blood pressure average real variability during 7-min of supine continuous blood pressure monitoring. The cross-sectional relationship between beat-to-beat BPV and hippocampal volumes, cognitive domain measures, and plasma biomarkers was assessed using multiple linear regression with adjustment for demographic covariates, vascular risk factors, and average systolic blood pressure. Elevated beat-to-beat BPV was associated with decreased left hippocampal volume ( P = .008), increased plasma concentration of glial fibrillary acidic protein ( P = .006), and decreased memory composite score ( P = .02), independent of age, sex, average systolic blood pressure, total intracranial volume, and vascular risk factor burden. In summary, beat-to-beat BPV is independently associated with decreased left hippocampal volume, increased neuroglial injury, and worse memory ability. Findings are consistent with prior studies examining visit-to-visit BPV and suggest beat-to-beat BPV may be a useful marker of hemodynamic brain injury in older adults.

A socio-spatial analysis of Australia's critical minerals endowment and policy implications - John Burton; Deanna Kemp; Rodger Barnes; Joni Parmenter (Resources Policy, 2024)

Horse fly and deer fly (Diptera: Tabanidae) species and abundance following logging in northwestern Ontario - Janette Buckley; James A. Schaefer; John L. Ringrose; Marco Raponi; Ian D. Thompson; Philip A. Wiebe; Art R. Rodgers; John M. Fryxell; David V. Beresford (Forest Ecology and Management, 2023)

Does air pollution confound associations between environmental noise and cardiovascular outcomes? - A systematic review - Katie Eminson; Yutong Samuel Cai; Yingxin Chen; Claire Blackmore; Georgia Rodgers; Nigel Jones; John Gulliver; Benjamin Fenech; Anna L Hansell (Environmental Research, 2023)

Modeling genetic benefits and financial costs of integrating biobanking into the conservation breeding of managed marsupials - Lachlan G. Howell; Peter R. Mawson; Pierre Comizzoli; Ryan R. Witt; Richard Frankham; Simon Clulow; Justine K. O'Brien; John Clulow; Paul Marinari; John C. Rodger (Conservation Biology, 2023)
Managed breeding programs are an important tool in marsupial conservation efforts but may be costly and have adverse genetic effects in unavoidably small captive colonies. Biobanking and assisted reproductive technologies (ARTs) could help overcome these challenges, but further demonstration of their potential is required to improve uptake. We used genetic and economic models to examine whether supplementing hypothetical captive populations of dibblers ( Parantechinus apicalis ) and numbats ( Myrmecobius fasciatus ) with biobanked founder sperm through ARTs could reduce inbreeding, lower required colony sizes, and reduce program costs. We also asked practitioners of the black‐footed ferret ( Mustela nigripes ) captive recovery program to complete a questionnaire to examine the resources and model species research pathways required to develop an optimized biobanking protocol in the black‐footed ferret. We used data from this questionnaire to devise similar costed research pathways for Australian marsupials. With biobanking and assisted reproduction, inbreeding was reduced on average by between 80% and 98%, colony sizes were on average 99% smaller, and program costs were 69‐ to 83‐fold lower. Integrating biobanking made long‐standing captive genetic retention targets possible in marsupials (90% source population heterozygosity for a minimum of 100 years) within realistic cost frameworks. Lessons from the use of biobanking technology that contributed to the recovery of the black‐footed ferret include the importance of adequate research funding (US$4.2 million), extensive partnerships that provide access to facilities and equipment, colony animals, appropriate research model species, and professional and technical staff required to address knowledge gaps to deliver an optimized biobanking protocol. Applied research investment of A$133 million across marsupial research pathways could deliver biobanking protocols for 15 of Australia's most at‐risk marsupial species and 7 model species. The technical expertise and ex situ facilities exist to emulate the success of the black‐footed ferret recovery program in threatened marsupials using these research pathways. All that is needed now for significant and cost‐effective conservation gains is greater investment by policy makers in marsupial ARTs.

The distribution and direct impacts of marine debris on the commercial shrimping industry - Alyssa Rodolfich; Eric Sparks; Ben Posadas; John Rodgers; Adam Skarke; Ryan Bradley; Caitlin Wessel (Marine Pollution Bulletin, 2023)

Monitoring trophic status using in situ data and Sentinel-2 MSI algorithm: lesson from Lake Malombe, Malawi - Rodgers Makwinja; Yoshihiko Inagaki; Tatsuyuki Sagawa; John Peter Obubu; Elias Habineza; Wendy Haaziyu (Environmental Science and Pollution Research, 2022)

High-resolution yeast quiescence profiling in human-like media reveals complex influences of auxotrophy and nutrient availability - Sean M. Santos; Samantha Laflin; Audrie Broadway; Cosby Burnet; Joline Hartheimer; John Rodgers; Daniel L. Smith; John L. Hartman (GeroScience, 2021)

Spatial and Temporal Changes in Emergent Marsh and Associated Marsh Birds of the Lower Mobile-Tensaw River Delta in Alabama, USA - Scott A. Rush; John Rodgers; Eric C. Soehren; John A. Trent (Wetlands, 2019)

Assessment of storm surge and structural damage on San Salvador Island, Bahamas, associated with Hurricane Joaquin (2015) - Christopher M. Fuhrmann; Kimberly M. Wood; John C. Rodgers (Natural Hazards, 2019)

Ecological niche models for sand fly species and predicted distribution of Lutzomyia longipalpis (Diptera: Psychodidae) and visceral leishmaniasis in Bahia state, Brazil - Moara de Santana Martins Rodgers; Maria Emilia Bavia; Eduardo Oyama Lins Fonseca; Bruno Oliveira Cova; Marta Mariana Nascimento Silva; Deborah Daniela Madureira Trabuco Carneiro; Luciana Lobato Cardim; John B. Malone (Environmental Monitoring and Assessment, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Quantitative PCR assays for detection of five arctic fish species: Lota lota, Cottus cognatus, Salvelinus alpinus, Salvelinus malma, and Thymallus arcticus from environmental DNA - Torrey W. Rodgers; John R. Olson; Stephen L. Klobucar; Karen E. Mock (Conservation Genetics Resources, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Solar Photocatalysis Using Fixed-Film TiO2 for Microcystins from Colonial Microcystis aeruginosa - Ciera M. Kinley; Maas Hendrikse; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Relationship among aqueous copper half-lives and responses of Pimephales promelas to a series of copper sulfate pentahydrate concentrations - Alyssa J. Calomeni; Ciera M. Kinley; Tyler D. Geer; Kyla J. Iwinski; Maas Hendrikse; John H. Rodgers (Ecotoxicology, 2018)

Cold tolerance and invasive potential of the redbay ambrosia beetle (Xyleborus glabratus) in the eastern United States - John P. Formby; John C. Rodgers; Frank H. Koch; Natraj Krishnan; Donald A. Duerr; John J. Riggins (Biological Invasions, 2018)

Microcystin-LR Degradation Following Copper-Based Algaecide Exposures - Ciera M. Kinley; Kyla J. Iwinski-Wood; Tyler D. Geer; Maas Hendrikse; Andrew D. McQueen; Alyssa J. Calomeni; Jenny Liang; Vanessa Friesen; Monique C. Simair; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Characterization of Copper Algaecide (Copper Ethanolamine) Dissipation Rates Following Pulse Exposures - Alyssa J. Calomeni; Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Maas Hendrikse; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Predicting In Situ Responses of Taste- and Odor-Producing Algae in a Southeastern US Reservoir to a Sodium Carbonate Peroxyhydrate Algaecide Using a Laboratory Exposure-Response Model - Tyler D. Geer; Alyssa J. Calomeni; Ciera M. Kinley; Kyla J. Iwinski; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Effects of Acid Volatile Sulfides (AVS) from Na2S-Amended Sediment on Hyalella azteca - Andrew D. McQueen; Ciera M. Kinley; Kyla J. Iwinski; Alyssa J. Calomeni; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Photocatalysis of a Commercial Naphthenic Acid in Water Using Fixed-Film TiO2 - Andrew D. McQueen; Ciera M. Kinley; Rebecca L. Kiekhaefer; Alyssa J. Calomeni; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2016)

Sediment Copper Concentrations, In Situ Benthic Invertebrate Abundance, and Sediment Toxicity: Comparison of Treated and Untreated Coves in a Southern Reservoir - Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Canopy interactions and physical stress gradients in subtidal communities - Scott Bennett; Thomas Wernberg; Thibaut de Bettignies; Gary A. Kendrick; Robert J. Anderson; John J. Bolton; Kirsten L. Rodgers; Nick T. Shears; Jean‐Charles Leclerc; Laurent Lévêque; Dominique Davoult; Hartvig C. Christie (Ecology Letters, 2015)
Species interactions are integral drivers of community structure and can change from competitive to facilitative with increasing environmental stress. In subtidal marine ecosystems, however, interactions along physical stress gradients have seldom been tested. We observed seaweed canopy interactions across depth and latitudinal gradients to test whether light and temperature stress structured interaction patterns. We also quantified interspecific and intraspecific interactions among nine subtidal canopy seaweed species across three continents to examine the general nature of interactions in subtidal systems under low consumer pressure. We reveal that positive and neutral interactions are widespread throughout global seaweed communities and the nature of interactions can change from competitive to facilitative with increasing light stress in shallow marine systems. These findings provide support for the stress gradient hypothesis within subtidal seaweed communities and highlight the importance of canopy interactions for the maintenance of subtidal marine habitats experiencing environmental stress.

Analysis of Algaecide Exposures: an Evaluation of the I3 − Method to Measure Sodium Carbonate Peroxyhydrate Algaecides - Ciera M. Kinley; John H. Rodgers; Kyla J. Iwinski; Andrew D. McQueen; Alyssa J. Calomeni (Water, Air, & Soil Pollution, 2015)

Natural and anthropogenic influence on soil erosion in a rural watershed in the Brazilian southeastern region - Anahí Chimini Sobral; Anna Silvia Palcheco Peixoto; Victor Fernandez Nascimento; John Rodgers; Alexandre Marco da Silva (Regional Environmental Change, 2015)

Responses of Planktothrix agardhii and Pseudokirchneriella subcapitata to Copper Sulfate (CuSO4 · 5H2O) and a Chelated Copper Compound (Cutrine®-Ultra) - Alyssa Calomeni; John H. Rodgers; Ciera M. Kinley (Water, Air, & Soil Pollution, 2014)

Biogeochemical Process-Based Design and Performance of a Pilot-Scale Constructed Wetland for Arsenic Removal from Simulated Bangladesh Groundwater - Jeffrey P. Schwindaman; James W. Castle; John H. Rodgers (Water, Air, & Soil Pollution, 2014)

Seasonal Performance of a Hybrid Pilot-Scale Constructed Wetland Treatment System for Simulated Fresh Oil Field-Produced Water - Bethany L. Alley; Ben Willis; John Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2013)

Bioavailability and Analytical Measurement of Copper Residuals in Sediments - Ben E. Willis; Bethany L. Alley; John H. Rodgers (Water, Air, & Soil Pollution, 2013)

Design and Performance of Pilot-Scale Constructed Wetland Treatment Systems for Treating Oilfield Produced Water from Sub-Saharan Africa - Jennifer E. Horner; James W. Castle; John H. Rodgers; Cynthia Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2012)

Treatment of Selenium in Simulated Refinery Effluent Using a Pilot-Scale Constructed Wetland Treatment System - Michael M. Spacil; John H. Rodgers; James W. Castle; Cynthia L. Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2011)

Plasma Membrane Integrity and Survival of Melanoma Cells After Nanosecond Laser Pulses - Francisco G. Pérez-Gutiérrez; Santiago Camacho-López; Rodger Evans; Gabriel Guillén; Benjamin S. Goldschmidt; John A. Viator; Guillermo Aguilar (Annals of Biomedical Engineering, 2010)

Dynamics of extracellular matrix in ovarian follicles and corpora lutea of mice - Helen F. Irving-Rodgers; Katja Hummitzsch; Lydia S. Murdiyarso; Wendy M. Bonner; Yoshikazu Sado; Yoshifumi Ninomiya; John R. Couchman; Lydia M. Sorokin; Raymond J. Rodgers (Cell and Tissue Research, 2010)

Characterization of Ash-Basin Waters from a Risk-Based Perspective - Lane Dorman; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2010)

Role of Equalization Basins of Constructed Wetland Systems for Treatment of Particulate-Associated Elements in Flue Gas Desulfurization Waters - Meg M. Iannacone; James W. Castle; John H. Rodgers (Water, Air, & Soil Pollution, 2009)

The Impact of Hurricane Katrina on the Coastal Vegetation of the Weeks Bay Reserve, Alabama from NDVI Data - John C. Rodgers; Adam W. Murrah; William H. Cooke (Estuaries and Coasts, 2009)

Chemical, Physical, and Risk Characterization of Natural Gas Storage Produced Waters - Brenda M. Johnson; Laura E. Kanagy; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2008)

The sensitivity of tree growth to air mass variability and the Pacific Decadal Oscillation in coastal Alabama - Jason C. Senkbeil; John C. Rodgers; Scott C. Sheridan (International Journal of Biometeorology, 2007)

Development, implementation, and evaluation of an international muskellunge management strategy for the upper St Lawrence River - John M. Farrell; Rodger M. Klindt; John M. Casselman; Steven R. LaPan; Robert G. Werner; Albert Schiavone (Environmental Biology of Fishes, 2007)

Applications of pedigree-based genome mapping in wheat and barley breeding programs - Mandy Christopher; Emma Mace; David Jordan; David Rodgers; Paul McGowan; Ian Delacy; Phillip Banks; John Sheppard; David Butler; David Poulsen (Euphytica, 2007)

Contributions of Schoenoplectus californicus in a Constructed Wetland System Receiving Copper Contaminated Wastewater - Cynthia L. Murray-Gulde; George M. Huddleston; Kristina V. Garber; John H. Rodgers (Water, Air, & Soil Pollution, 2005)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

The Responses of Selected Terrestrial Plants to Short (<12 days) and Long Term (2, 4 and 6 Weeks) Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) Exposure. Part I: Growth and Developmental Effects - Linda E. Winfield; John H. Rodger; Stephen J. D'surney (Ecotoxicology, 2004)

Cotton rat Sihi- M3 is a minimally oligomorphic Mhc I-b molecule that binds the chemotactic peptide fMLF under stringent conditions - C. Kuyler Doyle; Richard G. Cook; Robert R. Rich; John R. Rodgers (Immunogenetics, 2003)

Insulin-like effects of a physiologic concentration of carnitine on cardiac metabolism - Robert L. Rodgers; Michael E. Christe; George C. Tremblay; John R. Babson; Thomas Daniels (Molecular and Cellular Biochemistry, 2001)

Ritonavir: An Extraordinary Example of Conformational Polymorphism - John Bauer; Stephen Spanton; Rodger Henry; John Quick; Walter Dziki; William Porter; John Morris (Pharmaceutical Research, 2001)

Heterogeneity of RMA-S cell line: derivatives of RMA-S cells lacking H2-K b and H2-D b expression - Dewey Howell; Jonathan M. Levitt; Patricia A. Foster; Margaretha M. Guenther; Said M. Shawar; Robert R. Rich; John R. Rodgers (Immunogenetics, 2000)

Behavioural profiles in the mouse defence test battery suggest anxiolytic potential of 5-HT 1A receptor antagonists - G. Griebel; R. John Rodgers; Ghislaine Perrault; David J. Sanger (Psychopharmacology, 1999)

Effects of suspended solids on the bioavailability of chlordane toDaphnia magna - W. Scott Hall; Kenneth L. Dickson; Farida Y. Saleh; John H. Rodgers (Archives of Environmental Contamination and Toxicology, 1986)